Testing for exogeneity in nonlinear threshold models - George Kapetanios (Queen Mary University of London, Department of Economics, 2004)
Most work in the area of nonlinear econometric modelling is based on a single equation and assumes exogeneity of the explanatory variables. Recently, work by Caner and Hansen (2003) and Psaradakis, Sola, and Spagnolo (2004) has considered the possibility of estimating nonlinear models by methods that take into account endogeneity but provided no tests for exogeneity. This paper examines the problem of testing for exogeneity in nonlinear threshold models. We suggest new Hausman-type tests and discuss the use of the bootstrap to improve the properties of asymptotic tests. The theoretical properties of the tests are discussed and an extensive Monte Carlo study is undertaken.
Keywords: C12; C15; C22; 330; Threshold models; Endogeneity; Bootstrap; Monte-Carlo-Methode; Bootstrap-Verfahren; Nichtlineares Verfahren